2002
DOI: 10.1016/s0969-2126(02)00784-0
|View full text |Cite
|
Sign up to set email alerts
|

Accessory Protein Recruitment Motifs in Clathrin-Mediated Endocytosis

Abstract: Clathrin-mediated endocytosis depends upon the interaction of accessory proteins with the alpha-ear of the AP-2 adaptor. We present structural characterization of these regulatory interactions. DPF and DPW motif peptides derived from eps15 and epsin bind in type I beta turn conformations to a conserved pocket on the alpha-ear platform. We show evidence for a second binding site that is DPW motif specific. The structure of a complex with an AP-2 binding segment from amphiphysin reveals a novel binding motif tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
206
2
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(223 citation statements)
references
References 52 publications
14
206
2
1
Order By: Relevance
“…As seen in Figure 3B, EpsinR2C-13 bound to a-adaptin. Sequence analysis revealed that EpsinR2C-13 contains a DPF motif, which is the motif in animal epsin 1 that mediates binding to a-adaptin (Brett et al, 2002). To determine whether this motif was responsible for binding to a-adaptin, we generated an EpsinR2C-13 mutant in which the amino acids of the DPF motif were replaced with Ala (EpsinR2[DPF/AAA]).…”
Section: Epsinr2 Binds To A-adaptin and D-adaptinmentioning
confidence: 99%
“…As seen in Figure 3B, EpsinR2C-13 bound to a-adaptin. Sequence analysis revealed that EpsinR2C-13 contains a DPF motif, which is the motif in animal epsin 1 that mediates binding to a-adaptin (Brett et al, 2002). To determine whether this motif was responsible for binding to a-adaptin, we generated an EpsinR2C-13 mutant in which the amino acids of the DPF motif were replaced with Ala (EpsinR2[DPF/AAA]).…”
Section: Epsinr2 Binds To A-adaptin and D-adaptinmentioning
confidence: 99%
“…We next searched for motifs that mediate binding to clathrin adaptor proteins and found that Ocrl contains an FxDxF AP-2 binding motif at residues 151-155 (Fig. 4a) but no F͞WXXF AP-1 binding motif (18)(19)(20). GST binding assays with GST-AP-2␣, GST-AP-1␥, and GST-GGA2 (170-613) show that purified Ocrl directly interacts with AP-2␣ but only slightly with either AP-1␥ or GGA2 (Fig.…”
Section: Ocrl Binds To the ␣ Appendage Subunit Of Ap-2 (Ap-2␣) And Comentioning
confidence: 99%
“…This tract is considerably longer than the DP(FW) (41)(42)(43), FXDXF (43), and WXX(FW)X(DE) (44 -46) sequence motifs that engage the alternative AP-2 appendage, the ␣ subunit appendage (Table I). To determine whether this ARH sequence can interact with AP-2 in isolation, we fused either GLDEAFSRLAQSRTNP (GST-ARHM1) or VWELDDG-LDEAFSRLAQSRTNP (GST-ARHM2) in-frame with GST.…”
Section: Glumentioning
confidence: 99%